Understanding the impacts of the COVID-19 pandemic response measures on deaf adults in Cape Town - Slome, Charlotte (Department of Public Health and Family Medicine, 2023)
International literature has evidenced that Deaf people have been disadvantaged during the COVID-19 pandemic; however, there is currently no research published within the South African context. Deaf people, as both part of the disability community and a linguistic minority, have faced unique challenges during the COVID-19 pandemic, largely due to the implemented pandemic response measures. Such measures have included mask mandates, social distancing policies, hand hygiene guidelines, and lockdown protocols. This qualitative study investigated the ways in which the COVID-19 pandemic and its consequent response measures impacted Deaf adults in Cape Town. Semi-structured, in-depth interviews were held with fifteen Deaf/Hoh adults, who were recruited through the Deaf Community of Cape Town (DCCT) organisation. The interview schedule guided discussions to explore the perspectives, attitudes, and experiences of Deaf people on the implementation of COVID-19 response measures, assess the impact of response measures of Deaf persons' ability to communicate, access to and quality of health and social services, and access to Covid-19- related information. Professional SASL interpreters were used, and interviews were videotaped to capture the original, signed data and then transcribed by the researcher into English and stored on a password-protected drive. Fieldnotes were used as a complimentary method of data collection. The data were analysed using a thematic analysis approach in the N-Vivo software, firstly through a process of deductive coding, where pre-determined themes were applied to the data to generate codes, followed by inductive coding, which allowed codes and themes to emerge naturally from the content of the data. The findings focus on information provision, the impact of communication barriers on daily life, and how the response measures impacted access to and quality of healthcare. Overall, the findings demonstrate how the needs of the Deaf community were overlooked and their voices disregarded during the planning of the national response, ultimately having detrimental consequences.